Membaca Memahami Bahasa Jerman Melalui Media Quizizz - Wulandari Bintoen; Syamsu Rijal (Universitas Negeri Makassar, 2022)
Abstract. The purpose of this study was to obtain data and information on improving students' reading comprehension skills in German class X MIPA 2 SMA Negeri 16 Makassar through the application of Quizizz media. The research design used is Kurt Lewin's Classroom Action Research design which consists of four components: design, action, observation, and reflection. This research was conducted at SMA Negeri 16 Makassar with students of class X MIPA 2 consisting of 36 people as research subjects. The research data were collected through teacher activity observation sheets, student activity observation sheets and reading comprehension tests. The data in this study were analyzed using the average and percentage formula. The results of data analysis showed that the average value of students' reading comprehension skills in the first cycle was 69.17 which was classified in the less category. After making efforts to improve through maximizing the learning process in the second cycle using Quizizz media, the results showed that the average score of students in this cycle was 86.11 which was classified in the good category. The results of this study indicate that the Quizizz learning media can improve the ability to read and understand the students of class X MIPA 2 SMA Negeri 16 Makassar with a percentage increase of 16.94%.Keywords: Enhancement, Enhacement, read, German language, Quizizz